Work-life balance: a comparison of women in cardiology and other specialties. Issue 2 (21st July 2021) - Vlachadis Castles, Anastasia; Burgess, Sonya; Robledo, Kristy; Beale, Anna L; Biswas, Sinjini; Segan, Louise; Gutman, Sarah; Mukherjee, Swati; Leet, Angeline; Zaman, Sarah
Abstract : Objective: Significant gender disparities exist in some medical specialties, particularly cardiology. We assessed work, personal life and work-life balance in women in cardiology in Australia and New Zealand (NZ), compared with other specialties, to determine factors that may contribute to the lack of women in the specialty. Methods: This study is a prospective survey-based cohort study comparing cardiology and non-cardiology specialties. An online survey was completed by female doctors in Australia and NZ, recruited via email lists and relevant social media groups. The survey included demographics, specialty, stage of training, work hours/setting, children and relationships, career satisfaction, income and perceptions of specialty. Results: 452 participants completed the survey (median age 36 years), of which 57 (13%) worked in cardiology. Of all respondents, 84% were partnered and 75% had children, with no difference between cardiology and non-cardiology specialties. Compared with non-cardiology specialties, women in cardiology worked more hours per week (median 50 hours vs 40 hours, p<0.001), were more likely to be on call more than once per week (33% vs 12%, p<0.001) and were more likely to earn an annual income >3 00 000 (35% vs 10%, p<0.001). Women in cardiology were less likely to agree that they led a balanced life (33% vs 51%, p=0.03) or that their specialty was female friendly (19% vs 75%, p<0.001) or family friendly (20% vs 63%, p<0.001). Conclusions: Compared with other specialties, women in cardiology reported poorer work-life balance, greater hours worked and on-call commitments and were less likely to perceive their specialty as female friendly or family friendly. Addressing work-life balance may attract and retain more women in cardiology.